Generation and characterization of human U-2 OS cell lines with the CRISPR/Cas9-edited protoporphyrinogen oxidase IX gene - Novakova, Zora; Milosevic, Mirko; Kutil, Zsofia; Ondrakova, Marketa; Havlinova, Barbora; Kasparek, Petr; Sandoval-Acuña, Cristian; Korandova, Zuzana; Truksa, Jaroslav; Vrbacky, Marek; Rohlena, Jakub; Barinka, Cyril (Scientific reports, 2022)
In humans, disruptions in the heme biosynthetic pathway are associated with various types of porphyrias, including variegate porphyria that results from the decreased activity of protoporphyrinogen oxidase IX (PPO; E.C.1.3.3.4), the enzyme catalyzing the penultimate step of the heme biosynthesis. Here we report the generation and characterization of human cell lines, in which PPO was inactivated using the CRISPR/Cas9 system. The PPO knock-out (PPO-KO) cell lines are viable with the normal proliferation rate and show massive accumulation of protoporphyrinogen IX, the PPO substrate. Observed low heme levels trigger a decrease in the amount of functional heme containing respiratory complexes III and IV and overall reduced oxygen consumption rates. Untargeted proteomics further revealed dysregulation of 22 cellular proteins, including strong upregulation of 5-aminolevulinic acid synthase, the major regulatory protein of the heme biosynthesis, as well as additional ten targets with unknown association to heme metabolism. Importantly, knock-in of PPO into PPO-KO cells rescued their wild-type phenotype, confirming the specificity of our model. Overall, our model system exploiting a non-erythroid human U-2 OS cell line reveals physiological consequences of the PPO ablation at the cellular level and can serve as a tool to study various aspects of dysregulated heme metabolism associated with variegate porphyria.
Keywords: Aminolevulinic Acid; Humans; hem; Porphyria, Variegate; Protoporphyrinogen Oxidase; buněčné linie; protoporfyriny; kyselina aminolevulová; Heme; oxidoreduktasy; Oxidoreductases; protoporfyrinogenoxidasa; Cell Line; Protoporphyrins; porphyria variegata; CRISPR-Cas systémy; lidé; CRISPR-Cas Systems